TIPE DAN PROPORSI SALURAN PEMASARAN KOMODITI IKAN KEMBUNG (Rastrelliger sp) PADA PELABUHAN PERIKANAN SAMUDERA KENDARI - Restu Lia Sucianti; Akhmad Mansyur; Andi Irwan Nur; Sarini Yusuf; Azwar Sidiq (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
This study aims to determine the market share and type of marketing channels, as well as the proportion of marketing volume of mackerel (Rastrelliger sp) at the Kendari City Ocean Fisheries Port (PPS). This study was conducted in January-February 2024. The method used in this study was purposive sampling with descriptive analysis using a nominal and percentage approach. The types of data used were primary data and secondary data. Research data were obtained through observation, direct interviews, documentation and literature studies. The results of the study showed that the market share consists of two, namely the local market and the domestic market. The type of local market marketing channel consists of three types and the domestic market consists of one type. The highest proportion of marketing volume is in the local market in marketing channel II with a value of 73% and the lowest in marketing channel III with a value of 5%. The proportion of domestic market marketing volume has the same value in 2016-2019 at 100% while in 2020 it was 0% due to Covid-19. The highest proportion of market share is in the local market at 73% and the lowest in the domestic market at 27%.